2019
DOI: 10.3390/molecules24071374
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens Britton: A Comprehensive Study on Flavor/Taste and Chemical Properties During the Roasting Process

Abstract: This study investigated changes of volatile compounds, sniffing test-assisted sensory properties, taste associated-constituent and free amino acid compositions, taste description by electronic-tongue, and chemical characteristics in Perilla frutescens Britton var. acuta Kudo after roasting at 150 °C for 0–8 min. A total of 142 volatile compounds were identified, among which methyl benzoate and limonene were predominant, regardless of roasting time, and these were also detected as the major compounds in the sni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
4
17
1
Order By: Relevance
“…(2019) also found that arginine was the most abundant free amino acid and significantly decreased with roasting of Angelica gigas Nakai at 180°C for 0–5 min, which is in consistent with the result of this study ( p < .05). γ‐aminobutyric acid (GABA), a relatively common amino acid found in medicinal herbs such as Angelica gigas Nakai, Perilla frutescens Britton, and Cynanchi wilfordii Radix, was also observed in the present study (Kim et al, 2018; Kim et al., 2019; Lee et al., 2019). GABA is known to have sour taste and suppresses bitterness of organic compounds including quinone and caffeine (Ley, 2008).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…(2019) also found that arginine was the most abundant free amino acid and significantly decreased with roasting of Angelica gigas Nakai at 180°C for 0–5 min, which is in consistent with the result of this study ( p < .05). γ‐aminobutyric acid (GABA), a relatively common amino acid found in medicinal herbs such as Angelica gigas Nakai, Perilla frutescens Britton, and Cynanchi wilfordii Radix, was also observed in the present study (Kim et al, 2018; Kim et al., 2019; Lee et al., 2019). GABA is known to have sour taste and suppresses bitterness of organic compounds including quinone and caffeine (Ley, 2008).…”
Section: Resultssupporting
confidence: 76%
“…Similarly, Lee et al. (2019) reported that the content of alanine significantly decreased in Perilla frutescens Britton var. acuta Kudo when roasted at 150°C for 0–8 min, whereas hydroxylysine significantly increased ( p < .05).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations